Expanding language choices to reduce stigma: A Delphi study of positive and negative terms in substance use and recovery. Issue 1 (16th January 2019) - Ashford, Robert David; Brown, Austin; Curtis, Brenda
Abstract : Purpose: Public perception has been found to be influenced by the words used to describe those with behavioral health disorders, such that using terms like "substance abuser" can lead to higher levels of stigma. The purpose of this paper is to identify additional stigmatizing and empowering terms that are commonly used by different stakeholders. Design/methodology/approach: Using digital Delphi groups, the paper identifies positive and negative terms related to substance use disorder (SUD) from three distinct stakeholder groups: individuals in recovery, impacted family members and loved ones, and professionals in the treatment field. Findings: Participants identified 60 different terms that are considered stigmatizing or positive. Previously identified stigmatizing terms (abuser, addict) were present for all stakeholder groups, as was the positive term person with a SUD. Additional stigmatizing terms for all groups included junkie and alcoholic. Additional positive terms for all groups included long-term recovery. Social implications: The results suggest that the continued use of terms like addict, alcoholic, abuser and junkie can induce stigma in multiple stakeholders. The use of more positive terms such as person with a SUD or person in recovery is suggested to reduce stigma. Originality/value: The use of digital Delphi groups to solicit feedback from multiple stakeholder groups from the substance use community is innovative and allows for the comparison of linguistics among and between the groups.